Lipid Profile Status amongst the Pilots of Kuwait Air Force - Hossain, Nurunnabi Ibn; Rahman, Ashiqur; Ahmed, Farid Uddin (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Dyslipidemia has been established as one of the most important modifiable risk factors for cardiovascular diseases. Dyslipidemia is highly prevalent in the general population of Kuwait as well as in armed forces personnel. Objective: To assess the prevalence of dyslipidemia amongst the pilots of Kuwait Air Force. Materials and Methods: This descriptive cross-sectional study was carried out in Medical Directorate, Armed Forces Hospital Kuwait from July 2017 to June 2018. One hundred and twentysix Kuwaiti Air Force pilot were included in this study. Lipid profile [Total Cholesterol (TC), Triglyceride (TG), Low density lipoprotein cholesterol (LDL-C) and High density lipoprotein cholesterol (HDL-C)] were measured from fasting blood and were categorized based on the National Cholesterol Education Programme Adult Treatment Panel III criteria (NCEP-ATP III). Results: Mean (±SD) age of the 126 participants was 32.5±7.4 years. Among them 56.3% were current smoker. As per BMI (Body Mass Index) criteria 49.2% and 26.2% of the pilots were overweight and obese respectively. Most common lipid abnormality was high LDL-C (46%), followed by high TC (39.7%), low HDL-C 36.5%) and high TG (18.3%). Positive correlation between BMI and TG level and LDL-C level (r=0.273, p=0.001 & r=0.177, p=0.049 respectively) and negative correlation between BMI and HDL-C (r= -0.286, p=0.001) were found. BMI was found to be an independent predictive factor for dyslipidemia. Conclusions: Dyslipidemia and obesity was alarmingly high in the pilots of Kuwait Air Force and should be considered as a matter of medical concern. JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 71-75